Prospective Study on the Surgical Outcome of Eyelid Carcinoma: Oral Presentation - Observational Study - Ophthalmologist - HENING NALURIA (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Introduction Resection of eyelid carcinoma may lead to a risk of recurrences which might increase if excision was incomplete. Risk factors of incomplete surgical removal and recurrences are deep infiltration, spreading outside the macroscopic border, eye socket penetration, and histological type of the eyelid carcinoma. Objective To evaluate the surgical outcomes of eyelid carcinomas. Methods : This is a hospital based prospective observational study involving 16 patients. Prior to the surgery patients were evaluated for visual acuity, intra ocular pressure, extra ocular motility, fundus examination, and local clinical examinations. The eyelid carcinomas were histological detected concerning carcinoma type and margin involvement. Local anesthesia was applied. Patients were evaluated 1 month, 3 months and 6 months after surgery for local complications, patients satisfaction on surgical results, and recurrences. The surgical technic applied in this study were also observed. Results : Dominant tumor type were basal cell carcinoma and squamous cell carcinoma (87, 44%). The locations were at right and left lower eyelid with percentage of 68. 7 % and 31. 3 % respectively. All patients satisfied on surgery outcomes (100%). Three patients (6. 25 %) with complications were found within 6 months after the surgery. There were no recurrences during follow up period. Surgery procedures applied were modified hughe’s procedure (56. 25%) and mass excision and reconstruction (43. 75%). Conclusion : There was less complications and no recurrences within 6 months after surgery. All patients satisfied with the surgical outcomes.